Managing the learning and transfer of global management competence: Antecedents and outcomes of Japanese repatriation effectiveness - Furuya, Norihito; Stevens, Michael J; Bird, Allan; Oddou, Gary; Mendenhall, Mark (Journal of International Business Studies, 2009)
This study examines predictors that lead to effective individual learning of global management competencies on expatriate assignments and the transfer (i.e., the application of those competencies) in new assignments upon repatriation. A structural equation model based on data from 305 Japanese repatriates identifies linkages from organizational support, intercultural personality characteristics, self-adjustment, and repatriation policies to outcomes of global competency learning and transfer, which in turn lead to heightened job motivation and performance.